The Narrative Text as a Way to Strengthen the Communicative Competence of sfl - Aponte Buitrago, Andrea Lorena (Rastros Rostros, 2014)
This article presents various aspects of a research study into the teaching of Spanish as a Foreign Lan- guage (sfl), the objective of which was to strengthen the communicative competence of foreign sfl students through the use of different narrative texts: fables, tales, myths and legends. The project aimed to revise, apply and design a reading workbook with various narrative texts, along with exercises and activities. In terms of the methodology applied, this was an experimental study, and used an inductive method insofar as it involved the participation of a limited number of foreign students visiting Universidad Pedagógica y Tecnológica de Colombia (uptc) or the city of Tunja for both the application and analysis of results. It was found that the strategy of using narrative texts (fables, tales, myths and legends) helped improve sfl . Likewise, the foreign students found the texts to be appropriate, and the activities and exercises to be dynamic